Influence of rest interval between stretching and resistance training - Paz, Gabriel Andrade (2013)
Objective: To investigate the effect of different rest intervals between passive static stretching for quadriceps muscles and the performance of repetition maximum at 45° leg press and leg extension exercises. Methods: Sixteen trained women (22.2 ± 3.6 years, 57.2 ± 3.42 kg, 1.66 ± 32.3 cm) executed four sequences training on nonconsecutive days. PWI: initiated by static stretching followed by resistance exercises; P10: 10 minutes between static stretching and resistance exercises; P20: 20 minutes between static stretching and resistance exercises; PWS: the resistance exercises were performed without previous stretching. Results: A significant reduction in total maximum repetitions completed in PWI, P10 and P20 compared to PWS in the exercise of leg extension and leg press, except at P20 in the leg extension which showed no difference for the PWS. Conclusion: The 20 minute rest interval between static stretching and RT allowed a completely recovery of repetition performance for leg extension compared to PWS.